Microbial challenge test of a novel epoprostenol sodium formulation - Bandilla D; Goverde M; Giudici P; Lambert O (Dove Medical Press, 2017)
Dirk Bandilla,1 Marcel Goverde,2 Paolo Giudici,1 Olivier Lambert1 1Actelion Pharmaceuticals Ltd., Allschwil, 2MGP Consulting GmbH, Binningen, Switzerland Aim: The aim of the current study was to present a comprehensive display of antimicrobial activity of a novel epoprostenol sodium formulation with respect to seven different microorganisms, two levels of inoculation (102–103 colony forming units [CFU]/mL and 105–106 CFU/mL), two diluents (sterile water for injection [SWI] and sterile saline [sodium chloride 0.9%] for injection [SSI]), two concentrations (3,000 ng/mL and 15,000 ng/mL), and seven different storage time points at two temperatures (up to 10 days at 2°C–8°C and 20°C–25°C). Materials and methods: Antimicrobial activity was evaluated for, 1) solutions at 3,000 ng/mL inoculated with 102–103 CFU/mL and 105–106 CFU/mL; and 2) solutions at 15,000 ng/mL inoculated with 102–103 CFU/mL and 105–106 CFU/mL. All solutions were stored for up to 10 days at 2°C–8°C and 20°C–25°C. Solutions were prepared by reconstitution and further dilution of an epoprostenol sodium formulation using SWI or SSI. Antimicrobial activity was measured after inoculation with seven species of bacteria, yeast, and mold. Results: For all solutions, after 10 days, no microbial growth with respect to initial inoculum was observed, with the exception of a few early time points when using SWI as diluent. Some microorganisms died off completely, whereas others remained stable overall or returned to initial levels. Prior to decreasing, some microorganisms displayed a slight initial increase, presumed to be caused by breakup of clusters. Storage temperature had a negligible influence on the results, whereas choice of diluent (SSI or SWI) impacted growth kinetics in that SSI had a greater antimicrobial effect than SWI. Conclusion: Upon reconstitution and further dilution of the novel epoprostenol formulation to concentrations of 3,000 ng/mL and 15,000 ng/mL with SWI or SSI, the resulting solutions did not support growth of the tested microorganisms when stored at 2°C–8°C or 20°C–25°C for up to 10 days. Keywords: epoprostenol, preservative effectiveness, stability, microbial challenge